2016
DOI: 10.3109/10428194.2016.1141407
|View full text |Cite
|
Sign up to set email alerts
|

B-cell acute lymphoblastic leukemia with mature phenotype and MLL rearrangement: report of five new cases and review of the literature

Abstract: The association between mature-B phenotype and MLL abnormalities in acute lymphoblastic leukemia (ALL) is a very unusual finding; only 14 pediatric cases have been reported so far. We describe the clinical and biological characteristics and outcome of five pediatric cases of newly diagnosed B lineage ALL with MLL abnormalities and mature immunophenotype based on light chain restriction and surface Ig expression. Blasts showed variable expression of CD10/CD34/TdT. MLL abnormalities with no MYC involvement were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Our patient’s case represents an unusual situation where the extramedullary mass was biopsied with the expectation of a diagnosis of a primary non-haematological solid tumour, but instead revealed a haematological malignancy. While the MLL rearrangement has been shown to drive the development of extramedullary masses, and patients with the MLL rearrangement often are reported to have extramedullary involvement, the discrepancy in immunophenotype between the facial mass and bone marrow was not anticipated and on our review had not been reported previously 2 8 13. In this case, we hypothesise that the extramedullary mass was the less differentiated primary lesion and then subsequently a more differentiated clone metastasised to the bone marrow as the surface lambda expression was present in the marrow, but not in the mass.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Our patient’s case represents an unusual situation where the extramedullary mass was biopsied with the expectation of a diagnosis of a primary non-haematological solid tumour, but instead revealed a haematological malignancy. While the MLL rearrangement has been shown to drive the development of extramedullary masses, and patients with the MLL rearrangement often are reported to have extramedullary involvement, the discrepancy in immunophenotype between the facial mass and bone marrow was not anticipated and on our review had not been reported previously 2 8 13. In this case, we hypothesise that the extramedullary mass was the less differentiated primary lesion and then subsequently a more differentiated clone metastasised to the bone marrow as the surface lambda expression was present in the marrow, but not in the mass.…”
Section: Discussionmentioning
confidence: 60%
“…Unlike other pre-B ALL blasts, those with MLL rearrangement are commonly CD10 negative 7. A series of 19 cases of mature B-ALL with MLL rearrangements, surface Ig positivity and negative MYC rearrangements have been reported, of which 12 were CD10 negative and 12 were CD34 negative 8. Of these 19 cases, six were over 1 year of age at diagnosis, of which five were in complete remission at time of publication.…”
Section: Discussionmentioning
confidence: 99%
“…However, uncommon cases of BAL with expression of MLLr have been reported in children and adult [8,9]. In the study, we describe clinical feather, lab findings, treatment and prognosis of three MAL children with MLL-AF9 transcript, and we also reviewed 24 cases reports in literatures.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9,[17][18][19][20][21][22][23][24][25][26].Data of 27 patients suffered from BAL with MLLr, included the 3 patients in our articles, were collected and analyzed. 13 males and 14 females were included, the average or median age at diagnosis was 19.5 ±4.95 months or 12 months respectively (ranged from 6wk to 9yr), 14 (51.85%) or 24 (88.89%) patients were ≤1yr or ≤2yr respectively.…”
mentioning
confidence: 99%
“…MYCr is overexpressed in more than 95% of BL/BAL patients [2]. However, rare cases of BAL with MLLr expression have been reported in children and adults [8,9]. In this study, we describe the clinical features, lab ndings, treatment and prognosis of three children with MAL with MLL-AF9 transcripts, and we also reviewed 24 case reports in the literature.…”
Section: Introductionmentioning
confidence: 99%